The impact of internationalism on consumer ethnocentrism and purchase intentions: The moderating role of consumer personality among Sri Lankan consumers - Chethana, L.; Herath, N.H.M.S.M. (University of Colombo, 2025)
As globalization continues to influence consumer behavior, understanding how openness to foreign cultures (internationalism) shapes domestic purchasing decisions is increasingly important for emerging markets such as Sri Lanka. Consumer ethnocentrism, which reflects the belief that purchasing local products supports the national economy and preserves cultural identity, may be influenced by both sociocultural factors and individual psychological characteristics. In order to explore this further, this study examined the impact of internationalism on consumer ethnocentrism and purchase intentions of local products in Sri Lanka, with particular focus on the moderating role of consumer personality traits. Data were collected from a sample of 230 Sri Lankan consumers using a structured questionnaire. The survey measured levels of internationalism, consumer ethnocentrism, purchase intentions, and the Big Five personality traits - extraversion, agreeableness, neuroticism, openness to experience, and conscientiousness. The collected data were analyzed using SPSS through descriptive statistics, correlation, reliability and validity testing, and multiple regression techniques, including mediation and moderation analyses. The results revealed significant relationships between internationalism, consumer ethnocentrism, and purchase intentions. Specifically, internationalism was found to negatively influence purchase intention for domestic products while showing a positive relationship with consumer ethnocentrism. Consumer ethnocentrism positively affected local purchase intentions, and the mediation analysis confirmed that consumer ethnocentrism partially mediates the link between internationalism and purchase intention. Furthermore, personality traits moderated these relationships, suggesting that consumers with different psychological personalities respond differently to international exposure and ethnic orientations. This study contributes to the literature by integrating Social Identity Theory and the Big Five Personality Traits Model to explain how consumers perceive the global impact of their decisions and how personality traits influence variations in domestic product purchasing behaviour. The results provide valuable insights for marketers and policymakers in Sri Lanka, highlighting the need for marketing strategies that consider both cultural attitudes and personality differences. Marketers can use these findings to create targeted campaigns that appeal to ethnocentric consumers while also meeting the needs of those more open to global influences, ultimately fostering the growth of local industries in a competitive global marketplace.
Keywords: Internationalism; Consumer ethnocentrism; Consumer personality; Purchase Intention; Big Five Personality traits